Agricultural input subsidies for improving productivity, farm income, consumer welfare and wider growth in low‐ and lower‐middle‐income countries: a systematic review. Issue 1 (28th May 2018) - Hemming, David J.; Chirwa, Ephraim W.; Dorward, Andrew; Ruffhead, Holly J.; Hill, Rachel; Osborn, Janice; Langer, Laurenz; Harman, Luke; Asaoka, Hiro; Coffey, Chris; Phillips, Daniel
Abstract : This Campbell systematic review examines the effects of input subsidies on agricultural productivity, beneficiary incomes and welfare, consumer welfare and wider economic growth. The review summarizes evidence from 15 experimental and quasi‐experimental studies and 16 studies that use computable models, the majority concerning sub‐Saharan Africa. This review examines studies that evaluate the impact of agricultural input subsidies, including subsidies for agricultural machinery, seeds or fertilisers, on farmers, farm households, wage labourers or food consumers in low‐ or lower‐ middle‐income countries. It includes 15 experimental and quasi‐experimental studies and 16 simulation modelling studies. The majority relate to sub‐Saharan Africa (15 to Malawi) and to subsidised fertilizers and seeds. Fertiliser and seed subsidies are associated with increased use of these inputs, higher agricultural yields and increased income among farm households, but evidence of their effects on poverty is limited. There is much evidence that subsidy schemes are prone to inefficiency, bias and corruption. Models show that introducing or increasing subsidies generally results in positive effects for consumers and wider economic growth. However, the models indicate that the way subsidies are funded, world input prices and beneficiary targeting all have important influences on predicted outcomes. The authors were not able to find any studies examining subsidies for machinery. Plain language summary: Agricultural input subsidies raise input use, yields and farm income. The review in brief: Agricultural input subsidies raise input use, yields and farm income, but the evidence base is small and comes from a limited number of schemes and countries. What is this review about?: Greater use of improved seeds and inorganic fertilisers, and increased mechanisation, could boost agricultural productivity in some low‐ or lower‐middle‐income countries, but there is disagreement about whether subsidising these inputs is an effective way to stimulate their use. This review examines the evidence for impacts of input subsidies on agricultural productivity, beneficiary incomes and welfare, consumer welfare and wider economic growth. What is the aim of this review?: This Campbell systematic review examines the effects of input subsidies on agricultural productivity, beneficiary incomes and welfare, consumer welfare and wider economic growth. The review summarizes evidence from 15 experimental and quasi‐experimental studies and 16 studies that use computable models, the majority concerning sub‐Saharan Africa. What are the main findings of this review?: What studies are included?: This review examines studies that evaluate the impact of agricultural input subsidies, including subsidies for agricultural machinery, seeds or fertilisers, on farmers, farm households, wage labourers or food consumers in low‐ or lower‐ middle‐income countries. It includes 15 experimental and quasi‐experimental studies and 16 simulation modelling studies. The majority relate to sub‐Saharan Africa (15 to Malawi) and to subsidised fertilizers and seeds. What are the main results of this review?: Fertiliser and seed subsidies are associated with increased use of these inputs, higher agricultural yields and increased income among farm households, but evidence of their effects on poverty is limited. There is much evidence that subsidy schemes are prone to inefficiency, bias and corruption. Models show that introducing or increasing subsidies generally results in positive effects for consumers and wider economic growth. However, the models indicate that the way subsidies are funded, world input prices and beneficiary targeting all have important influences on predicted outcomes. The authors were not able to find any studies examining subsidies for machinery. What do the findings of this review mean?: Input subsidies can increase input use, and raise agricultural productivity with wider benefits. However, the design of subsidy schemes is crucial to their effectiveness, if they are to reach the desired farmers and stimulate input use. The effectiveness of subsidies in comparison to other interventions requires further study. A relatively small number of appropriate studies were found, and well‐documented research in countries beyond sub‐Saharan Africa is needed to ensure the wider relevance of these results. Mixed‐methods, theory‐based impact evaluations would help explore the impacts of different levels of subsidies for different beneficiaries. Simulation models studies could make more use of rigorous evidence from experimental and quasi‐experimental studies and examine more helpful subsidy comparisons. More clarity is needed in the reporting of methodological approaches, statistical information and the type and size of input subsidy implemented or modelled. How up‐to‐date is this review?: The review authors searched for studies up to 2013. This Campbell systematic review was published in 2018. Executive summary/Abstract: Background: In recent decades, agricultural productivity in low‐ and lower‐middle‐income countries, particularly in Africa, has fallen increasingly behind that of upper middle‐income countries. Adequate use of agricultural inputs such as improved seeds and inorganic fertilisers has been identified as one way of enhancing agricultural productivity. However, these inputs can be financially unaffordable or unattractive to many poor farmers in developing countries. Agricultural input subsidies aim to make inputs available to users at below market costs as a way of incentivising adoption, increasing agricultural productivity and profitability, increasing food availability and access and ultimately reducing poverty and stimulating economic growth. They were common in poor rural economies in the 1960s and 70s. Their use declined in the 1980s and 90s, but recent years have witnessed a resurgence of interest and investment, mainly in Africa. There remains considerable debate about the effectiveness and efficiency of their use and the conditions under which they may or may not work. Objectives: This systematic review explores the effects of agricultural input subsidies on agricultural productivity, farm incomes, consumer welfare and wider growth in low‐ and lower‐middle‐income countries. This research question is divided into the following primary and secondary research questions: 1. What are the effects of agricultural input subsidies on agricultural productivity and beneficiary incomes and welfare? 2. What are the effects of agricultural input subsidies on consumer welfare and wider economic growth? Search methods: We carried out a systematic search for includable studies in a wide range of sources and using a variety of search methods. We searched academic and online databases, carried out forwards and backwards citation tracking of included studies, and consulted experts. There were no restrictions on publication year, type or language, though searches were undertaken in English. The main searches were completed in November 2013. However, we incorporated additional papers after this date where they became available before our analysis was completed. Selection criteria: To be included, studies had to examine the effects of agricultural input subsidies, including products, machinery, seeds or fertilisers, on farmers, farm households, wage labourers or food consumers in low‐ or lower‐ middle‐income countries. Eligible comparisons included no active agricultural input subsidy intervention, wait‐list, alternate input subsidy intervention, or other interventions providing access to inputs. We included experimental or quasi‐experimental studies to address our primary research question regarding primary outcomes of adoption, productivity and farm income. We included econometric modelling studies to address our secondary research question on consumer welfare and wider economic growth outcomes. Studies were assessed by a single reviewer at both title and abstract level and full‐text level. A second reviewer then checked screening decisions taken at full‐text level. Data collection and analysis: We extracted a range of data including bibliographic details, outcomes, time period covered, study design and outcomes data. For our primary research questions we synthesised evidence from experimental and quasi‐experimental studies using meta‐analysis, meta‐regression analysis and a qualitative synthesis of relevant implementation and contextual factors. For our secondary research questions we synthesised evidence from modelling studies narratively and displayed effects in scatter plots where possible. Results: We identified 15 experimental and quasi‐experimental studies that assess the effectiveness of agricultural input subsidies on adoption, yield and farm incomes. We also identified 16 studies that use computable models that simulate the effect of agricultural input subsidies on measures of consumer welfare and wider growth. Overall, the evidence base is limited with a disproportionate focus on subsidy programmes in sub‐Saharan Africa and in particular on the case of Malawi. Most studies also have a focus on fertilisers and/or seeds rather than other types of inputs. We undertook meta‐analysis of experimental and quasi‐experimental studies to examine the effect of agricultural input subsidies on adoption, productivity, household income and poverty. The findings for primary outcomes are as follows: Adoption : Meta‐analysis of seven experimental and quasi‐experimental studies indicates an increase in adoption by 0.23 standard deviations (SD) (95% confidence interval (CI) [0.08, 0.38]) for farmers receiving agricultural input subsidies versus those not receiving agricultural input subsidies. Productivity : Across five studies, which were able to account adequate for confounding, there is an increase in yields of 0.11 SD (95% CI [0.05, 0.18]) for agricultural input subsidy recipients, compared to non‐recipients. Farm income : Recipient farmer income, measured by household expenditure and income and crop income and revenue from four studies, increases by 0.17 standard deviations (SD) (95% CI [0.10, 0.25]), over that of non‐recipients. Poverty : Only two studies report the effects of agricultural input subsidies on poverty, making it difficult to draw any clear conclusion. Meta‐regression found no association (positive or negative) between subsidy size and agricultural outcomes. However, narrative synthesis of data relating to programme implementation, input subsidy delivery mechanisms, farmer take‐up and usage of inputs, leakage of vouchers or inputs, and other associated factors indicates several points at which the theory of change for input subsidies breaks down. Subsidy vouchers do not always reach farmers in the quantities intended. Furthermore, where they do reach farmers they are not always used, and as a result providing subsidised inputs may not necessarily increase the amount of inputs used by farmers in absolute terms. We also synthesised data from simulation modelling studies of consumer welfare‐ and economic growth‐related outcomes including staple food prices and consumption, labour demand and agricultural wages, poverty incidence and gross domestic product (GDP). Results suggest that the relationships between the size of the change in subsidy and the outcomes of interest to be in line with our theory of change. However, analysis of modelling studies also indicates that factors such as how subsidies are funded, world input prices and beneficiary targeting can all play important roles in determining the effectiveness of input subsidies and their relative value compared to alternative policy options for agricultural development and poverty alleviation. Authors' conclusions: Implications for research: Overall, this review finds generally positive results for both primary and secondary outcomes across our theory of change. Included studies provide evidence linking fertiliser and seed subsidies to increased use of the subsidised inputs, higher agricultural yields and increased income among farm households, while the limited evidence relating to effects on poverty make it difficult to draw any clear conclusion. Models simulating subsidy effects show the introduction or increase in subsidies generally results in positive effects for consumers and wider economic growth. However, the review also indicates the importance of programme implementation and wider contextual factors. A narrative synthesis of data from experimental and quasi‐experimental studies finds implementation problems, with inputs not always made available or used as planned. Modelling studies indicate that the positive effects of subsidies are sensitive to changes in contextual factors endogenous and exogenous to the subsidy itself. There are also a number of implications for research. The review finds a relatively small evidence base of both experimental and quasi‐experimental studies, and econometric modelling studies. The evidence base focuses on a limited number of countries and evidence from a wider set of contexts where subsidies are used would be welcome. Implications for policy and practice: Mixed‐methods, theory‐based impact evaluations can explore different levels of subsidies and unpack outcomes and assumptions along the causal chain, for different sub‐groups of beneficiaries. Simulation models studies should make more use of rigorous evidence from experimental and quasi‐experimental studies in determining coefficients used for household behaviour and the micro‐economic effects of subsidies. Furthermore, including multiple simulations in modelling studies to offer a range of different possible scenarios may be of more use to policy makers rather than simple 'with or without subsidy' comparisons. Researchers should ensure that they more clearly report methodological approaches, relevant statistical information and the type and size of input subsidy implemented or modelled.